Increased serum S100A12 levels are associated with higher risk of acute heart failure in patients with type 2 diabetes. (11th August 2022) - Gellen, Barnabas; Thorin‐Trescases, Nathalie; Thorin, Eric; Gand, Elise; Ragot, Stephanie; Montaigne, David; Pucheu, Yann; Mohammedi, Kamel; Gatault, Philippe; Potier, Louis; Liuu, Evelyne; Hadjadj, Samy; et al.
Abstract: Aims: The hyperglycaemic stress induces the release of inflammatory proteins such as S100A12, one of the endogenous ligands of the receptors for advanced glycation end products (RAGE). Chronic activation of RAGE has multiple deleterious effects in target tissues such as the heart and the vessels by promoting oxidative stress, inflammation by the release of cytokines, macrophages infiltration, and vascular cell migration and proliferation, causing ultimately endothelial cell and cardiomyocyte dysfunction. The aim of our study was to investigate the prognostic value of circulating S100A12 beyond established cardiovascular risk factors (CVRF) for heart failure (HF) and major adverse cardiovascular events (MACE) in a cohort of patients with type 2 diabetes. Methods and results: Serum S100A12 concentrations were measured at baseline in 1345 type 2 diabetes patients (58% men, 64 ± 11 years) recruited in the SURDIAGENE prospective cohort. Endpoints were the occurrence of acute HF requiring hospitalization (HHF) and MACE. We used a proportional hazard model adjusted for established CVRF (age, sex, duration of diabetes, estimated glomerular filtration rate, albumin/creatinine ratio, history of coronary artery disease) and serum S100A12. During the median follow‐up of 84 months, 210 (16%) and 505 (38%) patients developed HHF and MACE, respectively. Baseline serum S100A12 concentrations were associated with an increased risk of HHF [hazard ratio (HR) (95% confidence interval) 1.28 (1.01–1.62)], but not MACE [1.04 (0.90–1.20)]. After adjustment for CVRF, S100A12 concentrations remained significantly associated with an increased risk of HHF [1.29 (1.01–1.65)]. In a sub‐analysis, patients with high probability of pre‐existing HF [N terminal pro brain natriuretic peptide (NT‐proBNP) >1000 pg/mL, n  = 87] were excluded. In the remaining 1258 patients, the association of serum S100A12 with the risk of HHF tended to be more pronounced [1.39 (1.06–1.83)]. When including the gold standard HF marker NT‐proBNP in the model, the prognostic value of S100A12 for HHF did not reach significance. Youden method performed at 7 years for HHF prediction yielded an optimal cut‐off for S100A12 concentration of 49 ng/mL (sensitivity 53.3, specificity 52.2). Compared with those with S100A12 ≤ 49 ng/mL, patients with S100A12 > 49 ng/mL had a significantly increased risk of HHF in the univariate model [HR = 1.58 (1.19–2.09), P  = 0.0015] but also in the multivariate model [HR = 1.63 (1.23–2.16), P  = 0.0008]. After addition of NT‐proBNP to the multivariate model, S100A12 > 49 ng/mL remained associated with an increased risk of HHF [HR = 1.42 (1.07–1.90), P  = 0.0160]. However, the addition of S100A12 categories on top of multivariate model enriched by NT‐pro BNP did not improve the ability of the model to predict HHF (relative integrated discrimination improvement = 1.9%, P  = 0.1500). Conclusions: In patients with type 2 diabetes, increased serum S100A12 concentration is independently associated with risk of HHF, but not with risk of MACE. Compared with NT‐proBNP, the potential clinical interest of S100A12 for the prediction of HF events remains limited. However, S100A12 could be a candidate for a multimarker approach for HF risk assessment in diabetic patients.